Potential markers of response to treatment of patients with chronic spontaneous urticaria - N. O. Pereverzina; E. O. Gribaleva; A. S. Allenova; D. M. Skander; P. V. Kolkhir (Лечащий Врач, 2021)
Chronic spontaneous urticaria (CSU) is characterized by wheals and/or angioedema arising spontaneously and persisting for at least 6 weeks. The recommended treatment options include second generation H1-antihistamine drugs (sgAH, as first- and second-line therapy), omalizumab and cyclosporine. Revealing of biomarkers of the response to treatment and their implementation into clinical practice may facilitate the treatment effectiveness and decrease the frequency of adverse events. The review of literature was conducted in MEDLINE/Pubmed electronic databases using the keywords «predictors AND treatment AND chronic urticaria», «biomarkers AND treatment AND chronic urticaria». 25 articles were included. It was found that baseline eosinopenia, basopenia and/or high level of C-reactive protein might predict the poor response to sgAH. Baseline eosinopenia, low levels of serum total IgE, positive results of autologous serum skin test, histamine release test and/or basophil activation test are associated with the poor response to omalizumab but good response to cyclosporine. Potential biomarkers of response to treatment in patients with CSU have been reported in the literature. However, randomized clinical trials are required before implementing the biomarkers into the routine clinical practice.